1987
DOI: 10.1242/dev.101.2.313
|View full text |Cite
|
Sign up to set email alerts
|

Movement of the multicellular slug stage of Dictyostelium discoideum; an analytical approach

Abstract: Time-lapse video recordings of migrating multicellular slugs of Dictyostelium discoideum were subjected to image analysis. A transient ‘collar-like’ structure was identified at the anterior end of the slug. This collar remains stationary in the wild- type strain WS380B; it is observed shortly after the advancing tip contacts the substratum. Stationary collars formed approximately every 12min; they were matched with patterns revealed on the underside of slime trails with FITC-coupled monoclonal antibody MUD50. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…3 ). As slugs migrate with their tips protruding vertically 52 , it may be easier to generate anterior responses to obstacles or enemies, such as nematodes 53 . Thus, it has been frequently observed that [Ca 2+ ] i is higher in the anterior than in the posterior of the slug.…”
Section: Discussionmentioning
confidence: 99%
“…3 ). As slugs migrate with their tips protruding vertically 52 , it may be easier to generate anterior responses to obstacles or enemies, such as nematodes 53 . Thus, it has been frequently observed that [Ca 2+ ] i is higher in the anterior than in the posterior of the slug.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, slugs travelling on agar move at a speed of 1-2 mm/h (~17 -34 µm/min) (Raper, 1940). Breen et al (1987) reported typical slug speeds of 30 µm/minat least twice that of solitary amoeba. Slug speeds vary proportionately to slug size and length Inouye and Takeuchi, 1979).…”
Section: Slug Speeds Higher Than Isolated Cellsmentioning
confidence: 99%